2004
DOI: 10.1086/380113
|View full text |Cite
|
Sign up to set email alerts
|

Tsunamis in Galaxy Clusters: Heating of Cool Cores by Acoustic Waves

Abstract: Using an analytical model and numerical simulations, we show that acoustic waves generated by turbulent motion in intracluster medium effectively heat the central region of a so-called ``cooling flow'' cluster. We assume that the turbulence is generated by substructure motion in a cluster or cluster mergers. Our analytical model can reproduce observed density and temperature profiles of a few clusters. We also show that waves can transfer more energy from the outer region of a cluster than thermal conduction a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Since the velocity amplitude is relatively large, the waves steepen and become weak shocks as shown in one-dimensional simulations (Fujita et al 2004b). Because of the pressure coming from the momentum of the waves, the coolest and densest gas noticeably shifts from the cluster center at Gyr, and the shift is clearly seen at t տ 0.7 Gyr (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Since the velocity amplitude is relatively large, the waves steepen and become weak shocks as shown in one-dimensional simulations (Fujita et al 2004b). Because of the pressure coming from the momentum of the waves, the coolest and densest gas noticeably shifts from the cluster center at Gyr, and the shift is clearly seen at t տ 0.7 Gyr (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Ruszkowski & Begelman 2002;Zakamska & Narayan 2003;Voigt & Fabian 2004;Conroy & Ostriker 2008;Bogdanović et al 2009;Ruszkowski & Oh 2010, 2011 and stirring by the motions of substructures (Fujita et al 2004;Ruszkowski & Oh 2011). However, the principle energy source is expected to be feedback from an accreting supermassive black hole (SMBH).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hydrodynamical simulations of merging clusters have shown that moving substructures can generate turbulence in the ICM by means of shearing instabilities (Roettiger et al 1997;Norman & Bryan 1999a;Takizawa 2000;Ricker & Sarazin 2001;Fujita et al 2004a;Takizawa 2005;Dolag et al 2005;Iapichino & Niemeyer 2008;Vazza et al 2009;Planelles & Quilis 2009).…”
Section: Introductionmentioning
confidence: 99%